Estimation of Glomerular Filtration Rate (GFR) in pregnant women - Patricia Fernández-Riejos; Catalina Sánchez-Mora; Raquel Galván Toribio; Carmen Rodriguez-Chacón; Antonio León-Justel (Archives of Renal Diseases and Management - Peertechz Publications, 2022)
Pregnancy induces marked changes in the cardiovascular and plasma volume regulatory systems. By the end of the first trimester of gestation, the kidneys show marked glomerular hyperfiltration, resulting in a decrease in the patient's serum creatinine with advancing gestational age [1].